Adverse consequences Following COVID-19 Vaccination - Zayer, Raheem Hussein (South Asian Journal of Social Sciences and Humanities, 2023)
Background: Employing a potent preventive measure stands as the sole recourse against COVID-19. The global scale of the COVID-19 pandemic has propelled an unparalleled rush in vaccine development. This pressing demand has spawned a diverse range of approaches in vaccine development considerations. Any potential adverse events from the COVID-19 vaccine are typical indicators that the body is building protection. Objectives: To identify the prevalence, types and to investigate the possible attributed factors for the adverse events associated with COVID-19 vaccines. Method: A descriptive cross-sectional study that was conducted in the Iraq / Baghdad / Al-Resafa Directorate of Health (DOH) from the 7th of April to the 5th of August 2021. A total of 420 participants were enrolled in the study. Results: The most prevalent adverse events were injection site tenderness and joint pain /lethargy. There was a significant association between the adverse event, time of disappearance, and the type of vaccine, the highest percentage was associated with Pfizer BioNTech. The adverse events were significantly higher in females. There was a significant association between the first and second doses regarding the prevalence of injection site tenderness, joint pain, fever, and other adverse events. Conclusion: Most vaccinated people developed mild adverse events, pain at the site of injection was the most prevalent adverse event. The gender and type of vaccine significantly affected the development of the adverse events.